A Study Interest In Technology Finance and E - Commerce - Afif, Ahmad Sururi; Yuliana; Hamzah, Ramadhani (Journal of Management, 2024)
The purpose of this study is to look at the relationship between financial literacy, financial technology, and interest in shopping in e-commerce (a case study of students from the Faculty of Economics and Business at Widyatama University who use the Tokopedia application). Quantitative research methodologies were used in this study, and the author employed a purposive sampling method. The sample size for this study was 82 respondents, and it focused on Tokopedia users who are also students at the Faculty of Economics and Business, Widyatama University in Bandung. The analytic approach is Multiple Linear Regression, and the research scale is a Likert scale. The findings of this study show that the Financial Literacy variable has a partially positive and significant effect on Shopping with a significant value, the Financial Technology variable has a positive and significant influence on Shopping Interest, and the Financial Attitude variable has a positive and significant impact on Shopping. Then, there is a favorable and considerable influence on Shopping Interest.